Assessment of the Geographic Distribution of Ornithodoros turicata (Argasidae): Climate Variation and Host Diversity. - Taylor G Donaldson; Adalberto A Pèrez de León; Andrew Y Li; Ivan Castro-Arellano; Edward Wozniak; William K Boyle; Reid Hargrove; Hannah K Wilder; Hee J Kim; Pete D Teel; Job E Lopez (PLoS Neglected Tropical Diseases, 2016)
BACKGROUND:Ornithodoros turicata is a veterinary and medically important argasid tick that is recognized as a vector of the relapsing fever spirochete Borrelia turicatae and African swine fever virus. Historic collections of O. turicata have been recorded from Latin America to the southern United States. However, the geographic distribution of this vector is poorly understood in relation to environmental variables, their hosts, and consequently the pathogens they transmit. METHODOLOGY:Localities of O. turicata were generated by performing literature searches, evaluating records from the United States National Tick Collection and the Symbiota Collections of Arthropods Network, and by conducting field studies. Maximum entropy species distribution modeling (Maxent) was used to predict the current distribution of O. turicata. Vertebrate host diversity and GIS analyses of their distributions were used to ascertain the area of shared occupancy of both the hosts and vector. CONCLUSIONS AND SIGNIFICANCE:Our results predicted previously unrecognized regions of the United States with habitat that may maintain O. turicata and could guide future surveillance efforts for a tick capable of transmitting high-consequence pathogens to human and animal populations.